Group A Streptococcus Prevents Mast Cell Degranulation to Promote Extracellular Trap Formation - Clark, Mary; Kim, Jessica; Etesami, Neelou; Shimamoto, Jacqueline; Whalen, Ryan V.; Martin, Gary; Okumura, Cheryl Y. M. (Frontiers in Immunology, 2018)
The resurgence of Group A Streptococcus (GAS) infections in the past two decades has been a rising major public health concern. Due to a large number of GAS infections occurring in the skin, mast cells (MCs), innate immune cells known to localize to the dermis, could play an important role in controlling infection. MCs can exert their antimicrobial activities either early during infection, by degranulation and release of antimicrobial proteases and the cathelicidin-derived antimicrobial peptide LL-37, or by forming antibacterial MC extracellular traps (MCETs) in later stages of infection. We demonstrate that MCs do not directly degranulate in response to GAS, reducing their ability to control bacterial growth in early stages of infection. However, MC granule components are highly cytotoxic to GAS due to the pore-forming activity of LL-37, while MC granule proteases do not significantly affect GAS viability. We therefore confirmed the importance of MCETs by demonstrating their capacity to reduce GAS survival. The data therefore suggests that LL-37 from MC granules become embedded in MCETs, and are the primary effector molecule by which MCs control GAS infection. Our work underscores the importance of a non-traditional immune effector cell, utilizing a non-conventional mechanism, in the defense against an important human pathogen.